Espace et marginalité Chez Libar Fofana - Mamadou Yaya SOW (Altralang Journal, 2023)
ABSTRACT: In his six novels, Guinean writer Libar Fofana endeavors to depict the conditions of women and marginalized people, perceived by the dominant opinion as second-class citizens. This article aims to illustrate how the stigmatization of these characters as minorities is intricately linked to the subdivision of space. This spatial division serves as a key to understanding the underlying conflicts within society, revolving around norms and values.